Regional unemployment and cyclical sensitivity in Spain - Almeida, Alejandro; Galiano, Aida; Golpe, Antonio A.; Martín-Álvarez, Juan Manuel (Letters in Spatial and Resource Sciences, 2020)
Unemployment has been routinely used as a measure of the economic cycle. In addition, regional unemployment rates are characterized by, among other factors, their relation to the national unemployment rate. In this regard, the literature on regional sensitivity to the economic cycle has analyzed how fluctuations in the national unemployment rate affect the regions. In recent years, due to the great impact of past crises, the development of new econometric techniques and the possible arrival of new crises, the debate on how sensitive regions are to the economic cycle has reopened. In Spain, this debate is necessary since unemployment rates are very high and display a great deal of heterogeneity. We analyzed regional unemployment rates in Spain between 1978 and 2018 through a recently developed dynamic spatial econometric model with common factors and found that some regions are more sensitive than others to the economic cycle. The results seem to show that in Spain, the sensitivity to the economic cycle displays a geographical pattern where the most sensitive regions are those located on the Mediterranean coast. Specifically, we find that the sensitivity to the economic cycle of unemployment is not determined by the fact that regions have high or low unemployment; it seems that geographical location plays an important role. These results can be useful for the national and regional governments when they implement countercyclical policies.
Keywords: common factor; cyclical sensitivity; regional unemployment; Spain; spatial dependence; Scopus; Emerging